An overview on recent advances in functional properties of dietary lipids, encapsulation strategies and applications - Jaydeep Dave; Ali Muhammed Moula Ali; Sri Charan Bindu Bavisetty (Nutrition & Food Science, 2022)
Purpose The purpose of this study was to provide contemporary scientific knowledge on the functionality of edible lipids, sources, health benefits, and a special emphasis on different encapsulation strategies to enhance their dietary application and boost the market value. Design/methodology/approach Novel technologies overcoming these issues are in great demand. Given that, several novel encapsulation techniques have been established aiming at most of the aspects of functional lipids. In addition, these techniques have been designed to enhance the storage stability and controlled release of lipids in food systems. Findings Plant and marine oils are one of the richest sources of functional lipids but are attached with limitations. Currently, alternative sources, such as different types of algae and microorganisms are gaining attention in terms of sustainable production systems. Advances in various encapsulation techniques have helped to overcome the dispersibility and stability problems of lipids encapsulation. Refinement in physicochemical interaction, colloidal dispersion and core-shell modules between wall and core matrix protect dietary lipids during processing have been implemented. Liposomes, micro/nanoemulsions and micro/nanocapsules are found most suitable for food application by improving the fatty acid profile, stability and sensorial properties. Originality/value Functional lipids offer numerous health benefits (i.e., simple health-promoting properties to complex disease preventive and curative effects). However, these functional lipids are associated with several disadvantages, such as region-specific availability, vulnerability to oxidation depending on the level of unsaturation, degradation/hydrolysis on processing, low bioavailability, confined storage stability, and others.
Keywords: Proteins in Food Systems; Food Chemistry and Fat Analysis; Microencapsulation and Drying Processes